Adolescents Self-Portrait and Self-Determination from Narative Perspective (Training and Practice : Journal of Educational Sciences, 2007)
The paper presents the theoretical background and partial results of a qualitative research focuses on the adolescents self-portrait. The research as part of the PhD dissertation - through self-naratives, self-caracterizations and methafores releted to self-knowledge- studies the spontaneous self-determination and selfrepresentation of students between ages 14-18, and follows a new perspective of self, namely the narative identity perspective, using the narative analyses in the context of an educational research. This paper focuses only on those research issues that are related to the adolescents main life-events. We were interested in naratives that are presented by the adolescents as having an important role in the process of self-determination and self-representation, and we focused on the social embedding, the role structure and the narative schemas used.